Frequency of Hepatitis B and C in Patients Reported at Al-Tibri Medical College & Hospital (Medical Forum Monthly, 2024)
Objective: The aim of this study is to determine the frequency of hepatitis B and C in the residents of Malir district who reported to Al Tibri Medical College & Hospital.Study Design: A Cross Section Prospective study.Place and Duration of Study: The study was conducted in the Department of Medicine and Pathology of Al Tibri Medical College & Hospital from May 2010 to April 2011.Materials and Methods: This study was based on the data of patients who reported to the hospital in a year. Pakistan is a developing country. On one side we have a population burden and on the other side communicable diseases. Viral Hepatitis is one of them. In general population the frequency of hepatitis B and C viral infection ranges from 8-15 %. Rapid Chromatography immunoassay and ELISA were the methods for the tests. The data was collected in a preset Performa and analyzed on SPSS version 16.Results: Total of 2093 specimen were reported. Both hepatitis B surface antigen and anti HCV antibody were checked. Total number of persons screened were 2093. Out of them male were 963 and female were 1130. HBV were 124 positive cases while 426 were anti HCV positive. This showed that HBs antigen were 5.9 % while Anti HCV antibody were 20.35 %. Among HBs Antigen positive cases 61 % were males while 39 % were females and in Anti HCV antibody positive cases the females were 67 % while 33 % were males. Hence combined infection were 2.7%. Cases were divided into five groups according to their ages. The group of ages between 25 to 45 had maximum positivity.Conclusion: The frequency of HBV and HCV in this particular area of our great province is quite high. This is the time to educate the general population of area so as to prevent the disease.